The future of Russia and Ukraine in the representations of russian intelligents of the civil war (on smallpublications in crimean newspapers 1919–1920 years) - S. B. Filimonov (Проблемы постсоветского пространства)
The work is dedicated to the 100th anniversary of the end of the Civil War inCrimea, which ended in the fall of 1920 with the Russian Exodus. The source significance of the newspapers published in the “white”Crimeain 1917–1920 is characterized and which became the result of the red terror of 1920–1921, when they were threatened with execution by bibliographic rarity, for the history of the domestic intelligentsia, science and culture. The presence in these newspapers of a significant number of publications of prominent and prominent Russian writers and scholars who are not listed in published bibliographic directories and therefore remained little known. The articles of Professor N. K. Gudzia, remaining little-known, “The End of Ukrainian Independence” and the writer S. Ya. Yelpatievsky, “Looking into the Future,” published in 1919–1920, before the formation of theUSSRin 1922, and devoted to thoughts on the future ofRussia, are being published. andUkraine. After the collapse of theUSSRin 1991, these articles again acquired extraordinary relevance.